Analisis Implementasi Kebijakan E-Filing Sebagai Upaya Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi Dalam Menyampaikan SPT Tahunan Di Kpp Pratama Depok Cimanggis Tahun 2021 - Wahyuningsih Wahyuningsih; Irawati Irawati (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to analyze how the implementation of the e-filing policy in an effort to improve the compliance of personal taxpayers in submitting annual tax returns at Depok Cimanggis Small Taxpayers Office in 2021, to analyze the barriers to the use of e-filing by personal taxpayers at Depok Cimanggis Small Taxpayers Office and to analyze efforts to improve the reporting of annual tax returns of individuals by filing at Depok Cimanggis Small Taxpayers Office. This research uses a qualitative approach. The data collection technique carried out is by conducting interviews with fiscus, academics and taxpayers related to the implementation of the e-filing policy, documentation and making observations at Depok Cimanggis Small Taxpayers Office. The results of this study concluded that the Implementation of the E-Filing Policy as an Effort to Improve Individual Taxpayer Compliance in Submitting Annual Tax Returns at Depok Cimanggis Small Taxpayers Office in 2021 in terms of communication is still lacking because the level of compliance of personal taxpayers is still very low, not comparable to the increase in the number of personal taxpayers registered at Depok Cimanggis Small Taxpayers Office and personal taxpayers who report annual tax returns e-filing declines in 2021. In terms of resources, Depok Cimanggis Small Taxpayers Office is good, the quality and quantity of human resources are adequate and understand the e-filing policy. In terms of the disposition of the e-filing policy, it is right on target, where the policy is intended for all taxpayers. In terms of bureaucracy, Depok Cimanggis Small Taxpayers Office has implemented the appropriate SOP where taxpayers who want to report the Annual Tax Return must first have an e-fin. Obstacles to the Implementation of the E-Filing Policy as an Effort to Improve Compliance of Personal taxpayers in Submitting Annual Tax Returns at Depok Cimanggis Small Taxpayers Office in 2021, namely servers that often go down when used jointly by taxpayers, there are still taxpayers who do not understand the reporting of annual tax returns through e-filing. The efforts made to overcome these obstacles are to make server improvements so that they do not go down when used jointly by taxpayers and carry out education, counseling and appeals to taxpayers to report annual tax returns on time so as to improve the compliance of personal taxpayers in reporting their Annual Tax Returns.